2016
DOI: 10.2495/eid160031
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment using landscape analysis methodology: the case of the Jundiaí Mirim river basin, Southeast Brazil

Abstract: Environmental damage and impacts from anthropogenic activities has led to the need for methodological development for its evaluation to subsidize environmental and human health management models. In this context, landscape analysis is a technique that incorporates a set of methods and procedures for understanding and explaining the structure, properties, indexes and parameters influenced by the occupation and use of the land. The main goal of this research was to present an environmental assessment methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 15 publications
1
4
0
15
Order By: Relevance
“…The behaviour of Fe was similar to that of Al, with inputs of this metal from the Atibaia River during SSIWT. Higher Fe concentrations were observed at sites P3 and P4, possibly due to anthropic influence (degradation of the river, soils and riparian forest), which contributed to transporting sediments to the river, as observed previously ( [20]).…”
Section: Metal Analysissupporting
confidence: 81%
See 2 more Smart Citations
“…The behaviour of Fe was similar to that of Al, with inputs of this metal from the Atibaia River during SSIWT. Higher Fe concentrations were observed at sites P3 and P4, possibly due to anthropic influence (degradation of the river, soils and riparian forest), which contributed to transporting sediments to the river, as observed previously ( [20]).…”
Section: Metal Analysissupporting
confidence: 81%
“…SSIWT raised the average turbidity by 219%, reflecting the cumulative effect of the increased flow along the Jundiaí-Mirim River, despite the lower turbidity observed in the water transferred from the Atibaia River (6.6 UNT). During SSIWT, there was an increase in around 1,400% from P1-Y to P4-Y, during the SSIWT, where Medeiros et al [20] reported undermining of the margins. From P4-Y to P5-Y, the turbidity decreased by 98.4%, because the reservoir behaved as a sediment decanter.…”
Section: Limnological and Chlorophyll-a Water Quality Parametersmentioning
confidence: 96%
See 1 more Smart Citation
“…Da mesma forma, na pesquisa, o projeto estruturante permitiu a integração das linhas de investigação em Recursos Hídricos e Recuperação Ambiental (BEGUELLI et al, 2015;MORAES;MACHADO et al, 2018;MEDEIROS et al, 2016), Modelagem ambiental e Recursos Hídricos (FRANÇA et al, 2014) e Modelagem Ambiental e Recuperação Ambiental (BRESSANE; ROVEDA; ROVEDA et al, 2015). Acrescente-se o desenvolvimento de atividades de integração entre as Ciências Sociais e as Ambientais, como as relacionadas à percepção ambiental (FENGLER; MEDEIROS; RIBEIRO et al, 2016), à abordagem construtivista (BRESSANE; MEDEIROS; RIBEIRO et al, 2015), à problematização (BRESSANE; RIBEIRO; MEDEIROS, 2015) e à aprendizagem por descoberta, como estratégias pedagógicas para promover a interdisciplinaridade nas Ciências Ambientais.…”
Section: B) Desenvolvimento De Atividades Integradas Das Disciplinasunclassified
“…Em 2013 e 2014, foram apresentados um total de 63 trabalhos, os quais foram publicados na forma de resumos expandidos. Tais resumos foram posteriormente desenvolvidos e se tornaram artigos publicados em periódicos científicos de abrangência nacional e internacional (BEGUELLI et al, 2015;MEDEIROS;RIBEIRO et al, 2016;FRANÇA et al, 2014;MACHADO et al, 2018;MEDEIROS et al, 2016).…”
Section: Workhop Seminário E Simpósio Realizadosunclassified